A biomechanical study of judo uchimata: a comparison of judokas with different skill levels - Hamaguchi, K.; Liu, L.; Shiokawa, M.; Deguchi, T. (Sports Biomechanics, 2025)
This study aimed to elucidate the biomechanical factors contributing to effective uchimata throwing by comparing highly skilled and less skilled judokas. Ten highly skilled and 10 less skilled judokas performed uchimata, with movement data recorded using a Mac3D motion analysis system (250 hz). The peak values of the body centre of mass velocity in the anterior-posterior and vertical directions were significantly greater in highly skilled judokas compared to their less skilled counterparts. Furthermore, the peak angular velocity of the hips, shoulders and arms, as well as the peak angular momentum of the technique recipient (uke), were significantly greater in highly skilled judokas than in less skilled ones. This suggests that judokas with advanced skills may execute throws more efficiently during throwing movements. Furthermore, a larger forward propulsion during the turning phase may be crucial in generating angular velocity in the hips, shoulders and arms during the throwing phase. Judo coaches should be aware of the accelerated body rotation during throwing that can be achieved by increasing the whole-body forward velocity. This insight can guide in enhancing the training protocol design when teaching uchimata and assist judokas in mastering the technique more efficiently.